The relevancy of mosque architecture in a multi-faith country-China as a case study - Ismail, Sumarni; Liu, Yuzhou; Asif, Nayeem; Sabil, Azmal (Abdullatif Al Fozan Award for Mosque Architecture and Institut Terjemahan & Buku Malaysia, 2019)
Islam had entered the land of China around 1400 years ago, and since then, Chinese Muslims are one of the minority group there. From the Tang dynasty until the present time, various cultural and geopolitical factors have influenced and shaped the architecture of Chinese Muslims. This paper reviews the chronological phases of mosque architecture in mainland China to elaborate on the process of adaptation and localization of Muslim architecture from ancient until modern times. Through comparison and discussion, this paper points out the inducing factors of the existing problems and puts forward some suggestions on the transformation of the function of urban mosques under the background of modernization